Preparation method and application of double-layer flexible structure molecular layer deposition coating

Through the preparation method of the double-layer flexible structure molecular layer deposition coating, the problem of single physical and chemical properties of the single-layer coating is solved, and the multiple properties of the double-layer coating are achieved, which significantly improves the circulation performance and capacity retention rate of the positive electrode material of lithium-ion battery.

CN119608528APending Publication Date: 2025-03-14GUANGDONG YUANNENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411539606.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the surface modified single-layer coatings performed by molecular layer deposition have single physical and chemical properties and cannot meet multiple requirements such as ion conduction, electron conduction, mechanical properties and chemical stability at the same time.

Method used

The preparation method of a double-layer flexible structure molecular layer deposition coating is adopted. By first depositing lithium polyol polymer, then depositing organic-inorganic composite polyurea, or inversely, a double-layer structure is formed, and the source entry time, carrier gas content and number of repeated circles of the precursor source are adjusted to control the thickness, composition and physical and chemical properties of each layer.

Benefits of technology

The double-layer coating takes into account both ionic conductivity and mechanical properties, improves the circulation performance of the positive electrode material and the first-circle Coulomb efficiency, and improves the capacity retention rate of long-term cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608528A_ABST
    Figure CN119608528A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a double-layer flexible structure molecular layer deposition coating. The preparation method comprises the following steps: firstly, screening a positive electrode material until particles are uniform; then putting the positive electrode material into a molecular layer deposition cavity, and preheating the positive electrode material to the temperature same as that of the cavity; adding a precursor, and preheating to enable all the required precursors to reach a target temperature; and finally, the double-layer structure is divided into two parts, namely a polyhydric alcohol lithium polymer and organic-inorganic composite polyurea, and molecular layer deposition is performed on the positive electrode particles according to the sequence of depositing the polyhydric alcohol lithium polymer and then depositing the organic-inorganic composite polyurea, or molecular layer deposition is performed on the positive electrode particles according to the opposite sequence. The double-layer flexible structure molecular layer deposition coating is obtained. The invention further discloses application of the double-layer flexible structure molecular layer deposition coating. The problem that in the prior art, when positive electrode particles are subjected to coating modification, the physicochemical property of a single-layer coating is single is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery positive electrodes, and specifically relates to a method for preparing a double-layer flexible structure molecular layer deposition coating. The present invention also relates to the application of the double-layer flexible structure molecular layer deposition coating. Background Art

[0002] Lithium-ion batteries are a type of electrochemical energy storage device. Due to their advantages of light weight, small size, and high energy, they are now widely used in small electronic devices, electric vehicles, and large-scale energy storage devices. The properties of electrode materials largely determine the quality of lithium-ion batteries, including cycle life, cost control, energy density, and other indicators.

[0003] As the core component of lithium battery, positive electrode materials determine the working voltage and capacity of the battery. At present, positive electrode materials include layered oxide materials, olivine-type iron lithium materials, spinel materials, etc. However, there are still many basic problems to be solved in the development of positive electrode materials, especially ternary high-nickel layered oxides, which face problems such as interface side reactions, particle mechanical crushing failure, and crystal structure changes.

[0004] Using molecular layer deposition to coat and modify cathode particles is an effective and common means to solve the current problems of cathode materials. However, the surface modification by molecular layer deposition reported so far is still limited by the single physical and chemical properties of the single-layer coating material, and cannot simultaneously meet the requirements for the coating properties such as ion conduction, electronic conduction, excellent mechanical properties, and high chemical stability. Therefore, it is imperative to find a molecular layer deposition interface design that can simultaneously meet multiple properties. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a double-layer flexible structure molecular layer deposition coating, which solves the problem of single physical and chemical properties of a single-layer coating when coating and modifying positive electrode particles in the prior art.

[0006] Another object of the present invention is to provide an application of a double-layer flexible structure molecular layer deposition coating.

[0007] The first technical solution adopted by the present invention is a method for preparing a double-layer flexible structure molecular layer deposition coating, which is specifically implemented according to the following steps: Step 1, sieve the positive electrode material until the particles are uniform; Step 2, placing the positive electrode material obtained in step 1 into a molecular layer deposition chamber, and preheating the positive electrode material to the same temperature as the chamber; Step 3, adding precursors and preheating to make all required precursors reach the target temperature; Step 4, the double-layer structure is divided into two parts: polyol lithium polymer and organic-inorganic composite polyurea. Molecular layer deposition is performed on the positive electrode particles in the order of first depositing the polyol lithium polymer and then depositing the organic-inorganic composite polyurea, or in the opposite order, molecular layer deposition is performed on the positive electrode particles to obtain a double-layer flexible structure molecular layer deposition coating.

[0008] The first technical solution of the present invention is also characterized in that: In step 1, the positive electrode material is one or more of lithium iron phosphate, ternary layered oxide positive electrode, lithium cobalt oxide, and lithium-rich positive electrode; in step 2, the chamber temperature is set to 20-200° C., an inert gas is used as a carrier gas, the carrier gas flow rate is set to 5-100 sccm, and the chamber is left to stand for 5 minutes.

[0009] In step 3, the preheating temperature of the lithium source precursor is 15~185°C, the pulse time is 0.1~2s, and the purge time is 10~60s. The preheating temperature of the polyol precursor is 15~100°C, the pulse time is 0.1~2s, and the purge time is 10~60s. The preheating temperature of the metal precursor is 15~185°C, the pulse time is 0.1~2s, and the purge time is 10~60s. The preheating temperature of the amine precursor is 15~100°C, the pulse time is 0.1~2s, and the purge time is 10~60s. The preheating temperature of the isocyanate precursor is 15~150°C, the pulse time is 0.1~2s, and the purge time is 10~60s; let it stand and wait for 5 minutes.

[0010] In step 3, the lithium source precursor is one or more of lithium tert-butoxide, lithium bis(trimethylsilyl)amide, lithium 2,2,6,6-tetramethyl-3,5-heptanedione, and LiOSiMe3.

[0011] In step 3, the polyol precursor is one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1-6-hexanediol, glycidol or glycerol.

[0012] In step 3, the metal precursor is one or more of trimethylaluminum, diethylzinc, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, or pentaethoxytantalum.

[0013] In step 3, the amine precursor is one or more of aminoethyl sulfide, ethylenediamine, 2,2'-(propane-2,2-diylbis(oxy))diethylamine, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine.

[0014] In step 3, the isocyanate precursor is one or more of 1,4-butyl diisocyanate and phenylene diisocyanate.

[0015] In step 4, the polyol lithium polymer layer has a lithium source precursor-polyol precursor as a cycle period, and the cycle period of atomic layer deposition is set to X. The range of X is a positive integer of 1-100.

[0016] The second technical solution adopted by the present invention is that the double-layer structure molecular layer deposition coating is applied to the liquid lithium-ion battery positive electrode material.

[0017] The beneficial effect of the present invention is that the preparation method of the double-layer flexible structure molecular layer deposition coating can take into account the ionic conductivity and mechanical properties of the coating. The thickness, composition and physical and chemical properties of each layer in the double-layer structure can be accurately controlled by adjusting the conditions such as the source entry time of the precursor source, the carrier gas content, and the number of repeated cycles. The preparation method is convenient and has strong repeatability. The method can improve the cycle performance attenuation of the positive electrode material during the charging and discharging process of the battery due to the instability of the interface, and can improve the ion transmission of the positive electrode interface, thereby improving the first cycle coulomb efficiency and improving the capacity retention rate of long-term cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The coated LiNi in Example 1 of the present invention 0.94 Mn 0.01 Co 0.05 Electrochemical performance test diagram of O2 and uncoated positive electrode materials in button cells; Figure 2 The coated LiNi in Example 2 of the present invention 0.94 Mn 0.01 Co 0.05 Electrochemical performance test diagram of O2 and uncoated positive electrode materials in button cells; Figure 3 The coated LiNi in Example 3 of the present invention 0.94 Mn 0.01 Co 0.05 Electrochemical performance test diagram of O2 and uncoated positive electrode materials in button cells; Figure 4 The coated LiNi in Example 4 of the present invention 0.94 Mn 0.01 Co 0.05 Electrochemical performance test diagram of O2 and uncoated positive electrode materials in button cells. DETAILED DESCRIPTION

[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0020] The preparation method of the double-layer flexible structure molecular layer deposition coating of the present invention is specifically implemented according to the following steps: Step 1: Use a metal sieve to sieve the positive electrode material until the particles are uniform; Step 2, placing the positive electrode material obtained in step 1 into a molecular layer deposition chamber, and preheating the positive electrode material to the same temperature as the chamber; Step 3, adding precursors and preheating to make all required precursors reach the target temperature; Step 4, the double-layer structure is divided into two parts: polyol lithium polymer and organic-inorganic composite polyurea. Molecular layer deposition is performed on the positive electrode particles in the order of first depositing the polyol lithium polymer and then depositing the organic-inorganic composite polyurea, or in the opposite order, molecular layer deposition is performed on the positive electrode particles to obtain a double-layer flexible structure molecular layer deposition coating.

[0021] The positive electrode material in step 1 is a common commercial positive electrode material, which is one or more of lithium iron phosphate, ternary layered oxide positive electrode, lithium cobalt oxide, and lithium-rich positive electrode; in step 2, the chamber temperature is set to 20-200°C, and is adjusted according to the different temperatures required for each layer in the double layer. An inert gas is used as a carrier gas, and the carrier gas flow rate is set at 5-100 sccm, and the chamber is left to stand for 5 minutes.

[0022] In step 3, the preheating temperature of the lithium source precursor is 15~185°C, the pulse time is 0.1~2s, and the purge time is 10~60s. The preheating temperature of the polyol precursor is 15~100°C, the pulse time is 0.1~2s, and the purge time is 10~60s. The preheating temperature of the metal precursor is 15~185°C, the pulse time is 0.1~2s, and the purge time is 10~60s. The preheating temperature of the amine precursor is 15~100°C, the pulse time is 0.1~2s, and the purge time is 10~60s. The preheating temperature of the isocyanate precursor is 15~150°C, the pulse time is 0.1~2s, and the purge time is 10~60s; let it stand and wait for 5 minutes.

[0023] In step 3, the lithium source precursor is one or more of lithium tert-butoxide, lithium bis(trimethylsilyl)amide, lithium 2,2,6,6-tetramethyl-3,5-heptanedione, and LiOSiMe3.

[0024] In step 3, the polyol precursor is one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1-6-hexanediol, glycidol or glycerol.

[0025] In step 3, the metal precursor is one or more of trimethylaluminum, diethylzinc, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, or pentaethoxytantalum.

[0026] In step 3, the amine precursor is one or more of aminoethyl sulfide, ethylenediamine, 2,2'-(propane-2,2-diylbis(oxy))diethylamine, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine.

[0027] In step 3, the isocyanate precursor is one or more of 1,4-butyl diisocyanate and phenylene diisocyanate.

[0028] In step 4, the polyol lithium polymer layer has a lithium source precursor-polyol precursor as a cycle period, and the cycle period of atomic layer deposition is set to X. The range of X is a positive integer of 1-100.

[0029] The organic-inorganic composite polyurea takes a metal precursor-amine precursor-isocyanate precursor-amine precursor as a cycle period, and the cycle period of atomic layer deposition is set to Y. The range of Y is a positive integer of 1-100.

[0030] Double-layer structure molecular layer deposition coating, applied to liquid lithium-ion battery positive electrode materials.

[0031] The raw materials and reagents used in the present invention are all commercially available.

[0032] Example 1 This embodiment contains Lithicone-AlPU double-layer coated LiNi 0.94 Mn 0.01 Co 0.05 The preparation method of O2 positive electrode is as follows: S1, LiNi 0.94 Mn 0.01 Co 0.05 The O2 positive electrode particles were placed in the molecular layer deposition chamber, the chamber temperature was raised to 150°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.

[0033] S2. Set the preheating temperature of the precursor lithium tert-butoxide to 175°C, the pulse time to 0.2s, and the purge time to 50s; set the preheating temperature of the precursor ethylene glycol to 85°C, the pulse time to 0.2s, and the purge time to 50s, take lithium tert-butoxide-ethylene glycol as one cycle, and repeat 2 times.

[0034] S3, then set the chamber to 65℃ and wait until the temperature is stable, the preheating temperature of trimethylaluminum is 25℃, the pulse time is 1s, the purge time is 50s, and the preheating temperature of the precursor 1,4-butyl diisocyanate is set to 90℃, the pulse time is 1s, and the purge time is 50s. Set the preheating temperature of the precursor ethylenediamine to 90℃, the pulse time is 1s, and the purge time is 50s. Deposition is carried out with trimethylaluminum-ethylenediamine-1,4-butyl diisocyanate-ethylenediamine as one cycle, and the number of turns is 2 turns.

[0035] S4, the coated LiNi prepared above 0.94 Mn 0.01 Co 0.05 O2 particles and PVDF binder, VGCF, C65 are prepared into slurry according to the mass ratio of 90:5:2.5:2.5 to prepare the positive electrode sheet. The mass loading of positive material is 5 mg / cm 2 .

[0036] S5. Dry the prepared positive electrode sheet in a vacuum oven with the temperature set to 110° C. and assemble the battery using a carbonate electrolyte.

[0037] Electrochemical performance test: The coated LiNi obtained in this example 0.94 Mn 0.01 Co 0.05 The electrochemical performance of O2 and uncoated positive electrode materials was tested in button cells. First, 3 cycles of charge and discharge activation were performed at a current of 0.1C (1C = 200mAh / g), and then a long cycle test was performed at a current of 0.5C. Figure 1 As shown, after 500 cycles at a current of 0.5C, the coated LiNi 0.94 Mn 0.01 Co 0.05 The cycle capacity retention rate of O2 positive electrode material has been significantly improved, with the capacity retention rate of 52.6% after 500 charge and discharge cycles, while the capacity retention rate of the uncoated positive electrode after 500 cycles is 29.3%.

[0038] Example 2 This example contains Lithicone-ZrPU double-layer coated LiNi 0.94 Mn 0.01 Co 0.05 The preparation method of O2 positive electrode is as follows: S1, LiNi 0.94 Mn 0.01 Co 0.05 The O2 positive electrode particles were placed in the molecular layer deposition chamber, the chamber temperature was raised to 150°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.

[0039] S2. Set the preheating temperature of the precursor lithium tert-butoxide to 175°C, the pulse time to 0.2s, and the purge time to 50s; set the preheating temperature of the precursor ethylene glycol to 85°C, the pulse time to 0.2s, and the purge time to 50s, take lithium tert-butoxide-ethylene glycol as one cycle, and repeat 2 times.

[0040] S3, then set the chamber to 65℃ and wait until the temperature is stable, the preheating temperature of tetra-tert-butyl zirconium oxide is 55℃, the pulse time is 1s, the purge time is 50s, and the preheating temperature of the precursor 1,4-butyl diisocyanate is set to 90℃, the pulse time is 1s, and the purge time is 50s. Set the preheating temperature of the precursor ethylenediamine to 90℃, the pulse time is 1s, and the purge time is 50s. Deposition is carried out with tetra-tert-butyl zirconium oxide-ethylenediamine-1,4-butyl diisocyanate-ethylenediamine as one cycle, and the number of turns is 2.

[0041] S4, the coated LiNi prepared above 0.94 Mn 0.01 Co 0.05 O2 particles and PVDF binder, VGCF, C65 are prepared into slurry according to the mass ratio of 90:5:2.5:2.5 to prepare the positive electrode sheet. The mass loading of positive material is 5 mg / cm 2 .

[0042] S3. Dry the prepared positive electrode sheet in a vacuum oven with the temperature set to 110° C. and assemble the battery using a carbonate electrolyte.

[0043] Electrochemical performance test: The coated LiNi obtained in this example 0.94 Mn 0.01 Co 0.05 The electrochemical performance of O2 and uncoated positive electrode materials was tested in button cells. First, 3 cycles of charge and discharge activation were performed at a current of 0.1C (1C = 200mAh / g), and then a long cycle test was performed at a current of 0.5C. Figure 2 As shown, after 500 cycles at a current of 0.5C, the coated LiNi 0.94 Mn 0.01 Co 0.05 The cycle capacity retention rate of O2 positive electrode material has been significantly improved, with the capacity retention rate of 45.9% after 500 charge and discharge cycles, while the capacity retention rate of the uncoated positive electrode after 500 cycles is 29.3%.

[0044] Example 3 This example contains Lithicone-ZnPU double-layer coated LiNi 0.94 Mn 0.01 Co 0.05 The preparation method of O2 positive electrode is as follows: S1, LiNi 0.94 Mn 0.01 Co 0.05 The O2 positive electrode particles were placed in the molecular layer deposition chamber, the chamber temperature was raised to 150°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.

[0045] S2. Set the preheating temperature of the precursor lithium tert-butoxide to 175°C, the pulse time to 0.2s, and the purge time to 50s; set the preheating temperature of the precursor ethylene glycol to 85°C, the pulse time to 0.2s, and the purge time to 50s, take lithium tert-butoxide-ethylene glycol as one cycle, and repeat 2 times.

[0046] S3, then set the chamber to 65℃ and wait until the temperature is stable, the preheating temperature of diethyl zinc is 25℃, the pulse time is 1s, and the purge time is 50s. Set the preheating temperature of the precursor 1,4-butyl diisocyanate to 90℃, the pulse time is 1s, and the purge time is 50s. Set the preheating temperature of the precursor ethylenediamine to 90℃, the pulse time is 1s, and the purge time is 50s. Deposition is carried out with diethyl zinc-ethylenediamine-1,4-butyl diisocyanate-ethylenediamine as one cycle, and the number of turns is 2 turns.

[0047] S4, the coated LiNi prepared above 0.94 Mn 0.01 Co 0.05 O2 particles and PVDF binder, VGCF, C65 are prepared into slurry according to the mass ratio of 90:5:2.5:2.5 to prepare the positive electrode sheet. The mass loading of positive material is 5 mg / cm 2 .

[0048] S5. Dry the prepared positive electrode sheet in a vacuum oven with the temperature set to 110° C. and assemble the battery using a carbonate electrolyte.

[0049] Electrochemical performance test: The coated LiNi obtained in this example 0.94 Mn 0.01 Co 0.05 The electrochemical performance of O2 and uncoated positive electrode materials was tested in button cells. First, 3 cycles of charge and discharge activation were performed at a current of 0.1C (1C = 200mAh / g), and then a long cycle test was performed at a current of 0.5C. Figure 3 As shown, after 500 cycles at a current of 0.5C, the coated LiNi 0.94 Mn 0.01 Co 0.05 The cycle capacity retention rate of O2 positive electrode material has been significantly improved, with the capacity retention rate of 40.7% after 500 charge and discharge cycles, while the capacity retention rate of the uncoated positive electrode after 500 cycles is 29.3%.

[0050] Example 4 This example contains AlPU-Lithicone double-layer coated LiNi 0.94 Mn 0.01 Co 0.05 The preparation method of O2 positive electrode is as follows: S1, LiNi0.94 Mn 0.01 Co 0.05 The O2 positive electrode particles were placed in the molecular layer deposition chamber, the chamber was set to 65°C and waited until the temperature stabilized.

[0051] S2, the preheating temperature of trimethylaluminum is 25℃, the pulse time is 1s, the purge time is 50s, and the preheating temperature of the precursor 1,4-butyl diisocyanate is set to 90℃, the pulse time is 1s, and the purge time is 50s. The preheating temperature of the precursor ethylenediamine is set to 90℃, the pulse time is 1s, and the purge time is 50s. The deposition is carried out with trimethylaluminum-ethylenediamine-1,4-butyl diisocyanate-ethylenediamine as one cycle, and the number of turns is 2.

[0052] S3, then raise the temperature of the chamber to 150°C and wait until the temperature remains stable. Set the carrier gas to argon, the carrier gas flow rate to 20 sccm, set the preheating temperature of the precursor lithium tert-butoxide to 175°C, the pulse time to 0.2s, and the purge time to 50s; set the preheating temperature of the precursor ethylene glycol to 85°C, the pulse time to 0.2s, and the purge time to 50s, and repeat 2 cycles.

[0053] S4, the coated LiNi prepared above 0.94 Mn 0.01 Co 0.05 O2 particles and PVDF binder, VGCF, C65 are prepared into slurry according to the mass ratio of 90:5:2.5:2.5 to prepare the positive electrode sheet. The mass loading of positive material is 5 mg / cm 2 .

[0054] S5. Dry the prepared electrode plates in a vacuum oven with the temperature set at 110° C. and assemble the battery using a carbonate electrolyte.

[0055] Electrochemical performance test: The coated LiNi obtained in this example 0.94 Mn 0.01 Co 0.05 The electrochemical performance of O2 and uncoated positive electrode materials was tested in button cells. First, 3 cycles of charge and discharge activation were performed at a current of 0.1C (1C = 200mAh / g), and then a long cycle test was performed at a current of 0.5C. Figure 4 As shown, after 500 cycles at a current of 0.5C, the coated LiNi 0.94 Mn 0.01 Co 0.05 The cycle capacity retention rate of O2 positive electrode material has been significantly improved, with the capacity retention rate of 39.7% after 500 charge and discharge cycles, while the capacity retention rate of the uncoated positive electrode after 500 cycles is 29.3%.

Claims

1. A method for preparing a double-layer flexible structure molecular layer deposition coating, characterized in that: Follow the steps below to implement it: Step 1, sieve the positive electrode material until the particles are uniform; Step 2, placing the positive electrode material obtained in step 1 into a molecular layer deposition chamber, and preheating the positive electrode material to the same temperature as the chamber; Step 3, adding precursors and preheating to make all required precursors reach the target temperature; Step 4, the double-layer structure is divided into two parts: polyol lithium polymer and organic-inorganic composite polyurea. Molecular layer deposition is performed on the positive electrode particles in the order of first depositing the polyol lithium polymer and then depositing the organic-inorganic composite polyurea, or in the opposite order, molecular layer deposition is performed on the positive electrode particles to obtain a double-layer flexible structure molecular layer deposition coating.

2. The method for preparing a double-layer flexible structure molecular layer deposition coating according to claim 1, characterized in that: In step 1, the positive electrode material is one or more of lithium iron phosphate, ternary layered oxide positive electrode, lithium cobalt oxide, and lithium-rich positive electrode; in step 2, the chamber temperature is set to 20-200° C., an inert gas is used as a carrier gas, the carrier gas flow rate is set to 5-100 sccm, and the chamber is left to stand for 5 minutes.

3. The method for preparing a double-layer flexible structure molecular layer deposition coating according to claim 1, characterized in that: In the step 3, the preheating temperature of the lithium source precursor is 15-185°C, the pulse time is 0.1-2s, and the purge time is 10-60s. The preheating temperature of the polyol precursor is 15-100°C, the pulse time is 0.1-2s, and the purge time is 10-60s. The preheating temperature of the metal precursor is 15-185°C, the pulse time is 0.1-2s, and the purge time is 10-60s. The preheating temperature of the amine precursor is 15-100°C, the pulse time is 0.1-2s, and the purge time is 10-60s. The preheating temperature of the isocyanate precursor is 15-150°C, the pulse time is 0.1-2s, and the purge time is 10-60s; stand and wait for 5 minutes.

4. The method for preparing a lithium battery positive electrode material protected by a double-layer structure molecular layer deposition coating according to claim 1, characterized in that: In step 3, the lithium source precursor is one or more of lithium tert-butoxide, lithium bis(trimethylsilyl)amide, lithium 2,2,6,6-tetramethyl-3,5-heptanedione, and LiOSiMe3; the polyol precursor is one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1-6-hexanediol, glycidol, or glycerol.

5. The method for preparing a lithium battery positive electrode material protected by a double-layer structure molecular layer deposition coating according to claim 1, characterized in that: In step 3, the metal precursor is one or more of trimethylaluminum, diethylzinc, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, or pentaethoxytantalum.

6. The method for preparing a lithium battery positive electrode material protected by a double-layer structure molecular layer deposition coating according to claim 1, characterized in that: In step 3, the amine precursor is one or more of aminoethyl sulfide, ethylenediamine, 2,2'-(propane-2,2-diylbis(oxy))diethylamine, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine.

7. The method for preparing a lithium battery positive electrode material protected by a double-layer structure molecular layer deposition coating according to claim 1, characterized in that: In step 3, the isocyanate precursor is one or more of 1,4-butyl diisocyanate and phenylene diisocyanate.

8. The method for preparing a lithium battery positive electrode material protected by a double-layer structure molecular layer deposition coating according to claim 1, characterized in that: In the step 4, the polyol lithium polymer layer has a cycle period of lithium source precursor-polyol precursor, and the cycle period of atomic layer deposition is set to X, where X is a positive integer ranging from 1 to 100.

9. The method for preparing a lithium battery positive electrode material protected by a double-layer structure molecular layer deposition coating according to claim 1, characterized in that: The organic-inorganic composite polyurea takes a metal precursor-amine precursor-isocyanate precursor-amine precursor as a cycle period, and sets the cycle period of atomic layer deposition to be Y, where the range of Y is a positive integer of 1-100.

10. Double-layer structure molecular layer deposition coating, characterized in that: Used in liquid lithium-ion battery positive electrode materials.